“A whole new language and a new world”: Seconded Teachers’ Experiences in a Faculty of Education - Reupert, Andrea; Wilkinson, Jane (Alberta Journal of Educational Research, 2011)
It is common practice in university faculties of education to second teachers for limited periods. However, few recent studies have examined how secondees perceive themselves in this role, particularly in relation to the increased demands to assume research as well as teaching duties. Three seconded school personnel were interviewed to explore their experiences of secondment in a faculty of education in Canada. One had previously been a teacher, one an educational consultant, and the third a principal. Qualitative data analysis revealed (a) the differences between schools and faculty; (b) the benefits of secondment for secondees and the institution; (c) secondees’ identity as teachers; (d) secondees’ mixed feelings about research; and finally (e) the drawbacks and issues in being seconded. Recommendations for future secondments and research directions conclude the article. Dans les facultés d'éducation à l'université, le détachement de personnel pour une période limitée constitue une pratique courante. Quelques études récentes portent sur la perception qu'ont les employés détachés de leur rôle, notamment en fonction de la hausse de demandes exigeant qu'ils accomplissent des tâches liées à la recherche en plus de celles relatives à l'enseignement. Nous avons interviewé trois membres du personnel scolaire détaché par rapport à leurs expériences de détachement dans une faculté de formation des enseignants au Canada. Parmi ces membres, il avait un ancien enseignant, un conseiller pédagogique et un directeur d'école. Une analyse qualitative des données a révélé: (a) les différences entre les écoles et le personnel; (b) les avantages du détachement pour les employés détachés et les institutions; (c) l'identité d'enseignant des employés détachés; (d) les sentiments ambivalents des employés détachés par rapport à la recherche; et finalement (e) les inconvénients et les enjeux liés au détachement. L'article conclut en présentant des recommandations qui visent les détachements et les orientations en recherche à l'avenir.